Formation of TiN dispersed composite layer on steel surfaces by Titanium Powder Preplacement and TIG Surface Melting Processes - Mridha, Shahjahan; Dyuti, S. (2011)
The possibility of forming a TiN dispersed composite layer on steel was studied by preplacement of titanium powder on steel surface and melting under TIG (Tungsten inert gas) torch in a reactive environment. The surface melting of preplaced 1.8 mg/mm2 Ti powder was performed under TIG torch with energy inputs of 324,378 and 432 J/mm in a pure nitrogen environment. With these melting conditions, the powder layer along with a thin layer of the substrate melted and produced a melt pool of around 1mm thickness. The resolidified melt layer consisted of dispersion of TiN dendrites in ferrite matrix and thus a composite of TiN in ferrite is created on the steel surface. The concentration of dendrite population was found to be higher nearer the melt surface compared to the deeper depth. A maximum surface hardness of about 2000 Hv was developed at the surface when glazed with an energy input of 432 J/mm and the hardness decreased gradually away from the surface. The hardness development is directly related to the concentration of TiN dendrites.